The Relationship Between Gadget Use and Digital Literacy Levels Among Elementary School Students - Muhammad Nazimuddin Al Kamil; Putriwanti Putriwanti; Mas'adi Mas'adi; Junita Christi Makawawa (Pedagogik Journal of Islamic Elementary School, 2025)
Gadget use among elementary school students is increasing in tandem with the advancement of digital technology. This study aims to determine the relationship between gadget use and the level of digital literacy of elementary school students. This research was conducted at SDN 2 Talise. This study used a quantitative approach with a correlational method. The sample consisted of 36 students selected purposively. The research instrument was a closed-ended questionnaire with a Likert scale, consisting of 15 items for the variables of gadget use and digital literacy. Data analysis included normality tests, linearity tests, and Pearson correlation tests. The results of the normality test indicated that the data were normally distributed, while the linearity test indicated a linear relationship between the two variables. The Pearson correlation test showed a significant positive relationship between gadget use and digital literacy. This finding suggests that the more frequent and appropriate use of gadgets, the higher the students' digital literacy level. This study emphasizes the importance of mentoring and educational use of gadgets to improve digital literacy skills from an early age.